2019
DOI: 10.1002/cbin.11194
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA HCG11 regulates cell progression by targeting miR‐543 and regulating AKT/mTOR pathway in prostate cancer

Abstract: Prostate cancer (PCa) is a common cancer worldwide, which mostly occurs in males over the age of 50. Accumulating evidence have determined that long non-coding RNA/microRNA (lncRNA/miRNA) axis plays a critical role in cell progression of cancers, including PCa. However, the pathogenesis of PCa has not been fully indicated. In this study, quantitative real-time polymerase chain reaction was used to detect the expression of HCG11 and miR-543. Western blot was applied to measure the protein expression of prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 28 publications
2
31
1
Order By: Relevance
“…Meanwhile, the protein expression of N-cadherin was found to be decreased and the protein expression of E-cadherin was increased after HCG11 upregulation in prostate cancer cells. 33 By contrast, we observed diminished N-cadherin and vimentin, yet restored E-cadherin expression in OS cells with HCG11 knockdown. The inconsistency may be caused by different microenvironments of the cancers.…”
Section: Discussioncontrasting
confidence: 58%
“…Meanwhile, the protein expression of N-cadherin was found to be decreased and the protein expression of E-cadherin was increased after HCG11 upregulation in prostate cancer cells. 33 By contrast, we observed diminished N-cadherin and vimentin, yet restored E-cadherin expression in OS cells with HCG11 knockdown. The inconsistency may be caused by different microenvironments of the cancers.…”
Section: Discussioncontrasting
confidence: 58%
“…LncRNA HCG11 has a wide range of biological roles. HCG11 can affect the proliferation, invasion, metastasis and apoptosis of tumor cells [10][11][12][13]. However, the role of HCG11 in atherosclerosis is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, overexpression of HCG11 has been found to inhibit cell proliferation, invasion and migration, whereas induce cell apoptosis in prostate cancer. 25 Here, we also found that upregulation of lncRNA HCG11 inhibited cell viability, migration and invasion in NSCLC. These findings indicated that lncRNA HCG11 acts as tumor suppressor in the development of NSCLC.…”
Section: Discussionsupporting
confidence: 56%